Значення мікросомального тригліцеридтранспортного протеїну в метаболізмі ліпідів - Панчишин, Ю.М.; Комариця, О.Й. (Медична гідрологія та реабілітація, 2009)
The microsomal triglyceride transfer protein plays an important role in the folding, assembling and secretion of lipoproteins that contain apoprotein B. Microsomal triglyceride transfer protein is necessary for the assembly and secretion of VLDL and when the protein is not functional, such as in abetalipoproteinaemia. Downstream effects resulting from this defect, include very low plasma cholesterol and triglyceride levels, absence of plasma apolipoprotein B and a lipid malabsorption syndrome, leading to lipo-soluble vitamin deficiencies. Deficiencies of these vitamins are known to cause a wide range of clinical effects ranging from blindness to coagulopathy and neuropathy.